2019
DOI: 10.1002/jcp.29391
|View full text |Cite
|
Sign up to set email alerts
|

GPX2 silencing relieves epithelial–mesenchymal transition, invasion, and metastasis in pancreatic cancer by downregulating Wnt pathway

Abstract: Glutathione peroxidase 2 (GPX2) participates in many cancers including pancreatic cancer (PC), and overexpression of GPX2 promotes tumor growth. Herein, we identified the role of GPX2 in epithelial–mesenchymal transformation (EMT), invasion, and metastasis in PC. Bioinformatics prediction was applied to select PC‐related genes. The regulatory function of GPX2 in PC was explored by treatment with short hairpin RNA against GPX2 or LiCl (activator of wingless‐type MMTV integration site [Wnt] pathway) in PC cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
1
24
0
1
Order By: Relevance
“…Interestingly, and in accordance t our ndings, reduced expression of GPX3 has been shown to be linked to increased proliferation rate in NSCLC by modulating redox mediated signals [105]. Further, GPX2 is associated with invasion, metastasis and tumor growth, as GPX2 knock down reduced levels of EMT markers such as vimentin, SNAI1 and MMP2 [106].…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, and in accordance t our ndings, reduced expression of GPX3 has been shown to be linked to increased proliferation rate in NSCLC by modulating redox mediated signals [105]. Further, GPX2 is associated with invasion, metastasis and tumor growth, as GPX2 knock down reduced levels of EMT markers such as vimentin, SNAI1 and MMP2 [106].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have described that GPX genes are critical for EMT, either preventing or enhancing it ( 23 – 25 ). Specifically, GPX2 downregulation is contrasting because it has been reported as a regulator of EMT markers, enhancing invasion, and metastasis targeting the Wnt pathway in cervical and pancreatic cancer ( 26 , 30 ). Nevertheless, NSCLC cells usually have an aberrant Wnt pathway, explaining why this could be different in these cells ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the transcriptional level, EMT downregulated the expression of GPX2 and GSR in A549, HCC827, and NCI-H358 cell lines. Furthermore, GSR and GPX genes have already been reported as essential features to block EMT in melanoma cells, cervical cancer, hepatocellular carcinoma, gastric, pancreatic, breast, and colon cancers ( 23 26 , 30 , 42 , 43 ). Hence, these findings supply evidence that the downregulation of GPX2 and GSR may be necessary for EMT induction on NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Moreover, EMT promotes tumor cell aggressiveness by increasing the expression of MMPs, especially gelatinases. 63 Thus, we hypothesized that Sal NPs can target cancer cells and CSCs through a gelatinasestimuli strategy. Previous studies have reported that our gelatinase-stimuli NPs showed superior performance as a delivery system for docetaxel or 5-fluorouracil.…”
Section: Discussionmentioning
confidence: 99%